Combining IL-10 and Oncolytic Adenovirus Demonstrates Enhanced Antitumor Efficacy Through CD8+ T Cells - Chen, Duo; Huang, Luyu; Zhou, Haiyu; Zhang, Yuhui (Frontiers in Immunology, 2021)
Oncolytic viruses are of growing importance in cancer therapeutics since they combine direct oncolytic effect and the stimulation of antitumor immunity. Emerging evidences showed that the function of oncolytic viruses is dependent on immune response in tumor microenvironment, and the modulation of immunity could influence their efficacy. Here we combined the interleukin 10 (IL-10) and oncolytic adenovirus Ad-hTERT to treat lung cancer and explored the underlying mechanism under combination therapy. Lewis lung carcinoma (LLC) and B16F10 tumor-bearing immunocompetent C57BL/6 mice that received Ad-hTERT or IL-10 alone showed mild antitumor effect, while the combination therapy shrink tumor bulks and prolonged survival remarkably. In addition, IL-10 didn’t show direct influence on tumor cell viability or Ad-hTERT mediated tumor cell lysis in vitro. To further explore the influence of combination therapy mediated antitumor capacity, we eliminated CD8+ T, CD4+ T or natural killer (NK) cells in LLC and B16F10-bearing C57BL/6 mice, and found that CD8+ T cells were critical mediator in the combination therapy. The combination therapy induced intensive infiltration of CD8+ T cells in tumors, increased tumor-specific IFN-γ secretion by CD8+ T cells. The long-term tumor-specific immune memory induced by the combination therapy rejected rechallenge by respective tumor cell lines. This study demonstrated that the therapy combining IL-10 and Ad-hTERT augmented antitumor efficacy which was CD8+ T cells dependent. Our findings paved the way to combine cytokines and oncolytic viruses to enhance antitumor immunotherapy in treating cancer.